DAMPAK POLUSI TERHADAP MAKHLUK HIDUP DALAM KARYA ILUSTRASI - YONANDO DEVANA, Yasrul Sami B, S.Sn., M.Sn., Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2019)
The purpose of the creation of this final work is to visualize the impact of pollution on living things. The method of creating works of art, using five stages, namely the preparation phase, the elaboration stage, the synthesis phase, the concept realization stage and the completion stage, and the last to hold an exhibition of paintings. The technique used is the aquarelle technique, placard and shading. The 10 titles of works that have been created are: 1. Burned Trees. 2. Their Home. 3. Human adn the Dying Little Tree’s Hope. 4. Polluted City. 5. Their Home. 6. No Fertile Soil for Planting. 7. No Fresh Air. 8. Black Cloud. 9. Smoky Sunset. 10. Polluted Water.Kata kunci :Pollution, Impact, Illustration